SISTEM SENSUS BERBASIS WEB DAN ANDROID PADA BADAN PUSAT STATISTIK - Zaryanti Zainuddin; Furqan Zakiyabarsi; Annisa Nurul Puteri (Universitas Fajar, 2016)
This research aims to design a web-based census system and android on the agency Statistics Center. To achieve these objectives used methods of data collection in the form of file documentation and interviews.In the design of the library information system the author makes the design of Data Flow Diagrams (DFD), and Use Case.The results showed that the system is census-based web and android that has been created consisting of administrators, enumerators, and the user is easier for officers to perform data entry enumerators, inputting to the census, the recapitulation of the census of education and health, the presentation of data to the census, as well as easier for people to looking for information in the form of data needed to realize the census data processing system that is efficient, effective, and mobile